Transformasi Tradisi Baritan: Antara Pelestarian Budaya dan Potensi Pemberdayaan Masyarakat - Misnen Misnen; Dian Tias Aorta (YASIN, 2026)
Although the Baritan tradition remains an important part of the social life of the Wati Hamlet community, the dynamics of modernization pose challenges to its sustainability, youth participation, and the development of its social functions. This study aimed to analyze the existence and transformation of the Baritan tradition in the social life of the Wati Hamlet community and to identify empowerment potential that can be developed amid social change. This study used a qualitative approach with a case study method. Data were collected through interviews, observation, and documentation, with participants consisting of customary leaders, community members, and young people selected purposively. The results showed that the Baritan tradition continues to survive as a cultural practice with strong spiritual and social values, particularly mutual cooperation, togetherness, and gratitude. However, the sustainability of this tradition faces challenges in the form of low youth participation, the influence of globalization, and limited documentation and promotion. On the other hand, the Baritan tradition has the potential for community empowerment through simple economic activities and community-based cultural development, although its implementation has not yet been optimal. The conclusion of this study confirms that the Baritan tradition has undergone a transformation from a cultural ritual toward a broader social function, thereby offering opportunities to be developed as a basis for community empowerment and the preservation of local wisdom amid modernization.